Wetu Telu in Bayan Lombok: - Zuhdi, Muhammad Harfin (Kawalu: Journal of Local Culture, 2016)
Islam reached Lombok Island in the sixteenth century, approximately in 1545, which was brought by SunanGiri, the son of SunanPrapen, one of the prominent Islamic preachers known as Wali Songo, through an expedition from Java. Prior to its arrival in the Island, according to some historians, the indigenous Sasak (the indigenous people of Lombok) embraced a traditional belief known as Boda. Historically, since its establishment, Islam has perpetually been expanding despite facing some distinct and contradictory values of local tradition and culture, which leads to a kind of dialectical process and turns in what is known as local Islam such as Islam WetuTelu in Bayan, West Lombok. This article is aimed at revealing the historical root of religious identity of Sasak community. The historical sketch of its religious identity produces a combination of traditional, cultural and religious values of the comers with those of the indigenous people in the past, WetuTelu religion. Present Muslims in Lombok assume that the existence of traditional Islam is due to an incomplete process of Islamization in the Island. Keywords: Boda, Agama, Local culture, WetuTelu, Waktu Lima